2016
DOI: 10.3319/tao.2016.05.02.01
|View full text |Cite
|
Sign up to set email alerts
|

Summer Convective Afternoon Rainfall Simulation and Projection Using WRF Driven by Global Climate Model. Part I: Over Taiwan

Abstract: This paper is the first of a two-part study that investigates summer convective afternoon rainfall (CAR) activity over the East Asian continent through simulation and projection. We focus on the CAR activity over Taiwan in Part I. In Part II, the changes in CAR activity over South China and Luzon are examined. Using the WRF (Weather Research and Forecasting) model driven by two super-high resolution global climate models: HiRAM (High Resolution Atmospheric Model) and MRI (Meteorological Research Institute Atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
2
19
0
Order By: Relevance
“…2d), the results show that both the diurnal rainfall over South China and Luzon tend to reach their maximum at 17 LT. This feature is similar to that revealed over Taiwan (Huang et al 2016). In view of previous studies (e.g., Kikuchi and Wang 2008), one frequently adopted method to illustrate major diurnal rainfall features over a larger domain is to apply an Empirical Orthogonal Function (EOF) analysis on the 3-hourly rainfall.…”
Section: Observed and Simulated Diurnal Rainfall Variationssupporting
confidence: 72%
See 4 more Smart Citations
“…2d), the results show that both the diurnal rainfall over South China and Luzon tend to reach their maximum at 17 LT. This feature is similar to that revealed over Taiwan (Huang et al 2016). In view of previous studies (e.g., Kikuchi and Wang 2008), one frequently adopted method to illustrate major diurnal rainfall features over a larger domain is to apply an Empirical Orthogonal Function (EOF) analysis on the 3-hourly rainfall.…”
Section: Observed and Simulated Diurnal Rainfall Variationssupporting
confidence: 72%
“…Finally, we examine what causes the projected changes in CAR frequency over South China and Luzon. In view of part I of this two-part investigation (Huang et al 2016), it is suggested that the changes in daytime surface wind convergence and thermal instability are the two major factors that modulate the changes in CAR frequency over Taiwan. To know if this suggestion can be applied to explain the changes in CAR frequency over South China and Luzon, we examined the projected changes in daytime surface wind convergence (Figs.…”
Section: Projected Change In Car Activitymentioning
confidence: 99%
See 3 more Smart Citations